Fiscal Policy and Stock Market Development in an Emerging West African Economy: The Case of Nigeria - Nwakobi, Dr. Paschal Chikwado; Ananwude, Amalachukwu; Umezurike, Chinedu Maurice (Finance & Economics Review, 2020)
Purpose: This article presents a study on the effect of fiscal policy on stock market development in an emerging West African economy with an emphasis on Nigeria for the period of 1986 to 2018. Specifically, we evaluated the effect of fiscal deficit on all share index including government total expenditure on market capitalization ratio, the value of stock traded, and turnover ratio using data from the Central Bank of Nigeria (CBN) and Nigerian Stock Exchange (NSE). Methods: The Auto-regressive Distributive Lag (ARDL) was the estimation technique employed in ascertaining the nature of the short-run relationship between fiscal policy and stock market development indices, whereas the effect of fiscal policy on stock market development was actualized under the granger causality analysis. Results: The result of the analysis revealed that fiscal deficit has no significant effect on all share index; government total expenditure has no significant effect on stock market capitalization ratio; government total expenditure has a significant effect on the value of stock traded ratio; government total expenditure has no significant effect on the stock market turnover ratio. Implication: Government should implement its fiscal policies to carefully accommodate the development of the stock market, as changes in fiscal policy affect the overall activities in the market and ultimately the economy.